2018
DOI: 10.1016/j.gheart.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

INR Control of Patients with Mechanical Heart Valve on Long-Term Warfarin Therapy

Abstract: Despite a majority of patients having <60% TTR, there were low incidences of bleeding and stroke events in this center. There were no factors found to be associated with INR control in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
3
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
0
8
3
2
Order By: Relevance
“…A prior retrospective study demonstrated a mean TTR of 72.5% in Swedish patients with mechanical heart valve prosthesis; another study showed that the mean TTR was 47.48% in Malaysian patients with mechanical heart valve(s) replacement. 26,27 The mean TTR in patients with PHV in this study was 30.5%, which was lower than the previously reported rate. Our study also demonstrated that warfarin control was worse in patients with PHV than in patients with AF.…”
Section: Status Of Warfarin Control In Hong Kongcontrasting
confidence: 77%
“…A prior retrospective study demonstrated a mean TTR of 72.5% in Swedish patients with mechanical heart valve prosthesis; another study showed that the mean TTR was 47.48% in Malaysian patients with mechanical heart valve(s) replacement. 26,27 The mean TTR in patients with PHV in this study was 30.5%, which was lower than the previously reported rate. Our study also demonstrated that warfarin control was worse in patients with PHV than in patients with AF.…”
Section: Status Of Warfarin Control In Hong Kongcontrasting
confidence: 77%
“…A 5-year retrospective cohort study from Swedish registries reported a mean TTR of 72.5% in patients with mechanical heart valve prosthesis, while another study in Malaysia showed that mean TTR in patients with mechanical heart valve(s) replacement was 47.48%. 34,35 Mean TTR in patients with PHV in this study was 30.5%, lower than the previously reported findings. Our study also demonstrated that warfarin control in patients with PHV was worse that patients with AF.…”
Section: Status Of Warfarin Control In Hong Kongcontrasting
confidence: 80%
“…. Out of 259 patients,35.9% of subjects experienced complications including thrombotic events and bleeding complications.Out of the 39 patients with thrombotic events, 41.0% of them had recurrent non-ST elevation myocardial infarction and 33.3% had stroke. For bleeding complications, 68.8% had minor bleeding while 31.3% of them experienced major bleeding episodes.…”
mentioning
confidence: 99%
“…Among patients with atrial fibrillation, studies have shown an association between low quality of VKA treatment and the risk of outcomes, whereas studies on patients with mechanical heart valve have shown contradictory results. [8][9][10][11] This nationwide, carefully designed study set out to examine the association between TTR and the risk of thromboembolic events and bleeding in patients with mechanical valve prostheses.…”
Section: Perspectivementioning
confidence: 99%
“…Results: In total, 659 patients undergoing mechanical heart valve replacement were included in the study. Median number of international normalized ratio measurements in the 6-month period after surgery was 13 (interquartile range, [8][9][10][11][12][13][14][15][16][17][18][19]. Median TTR was 54.9% (interquartile range, 39.0%-72.9%) and 29.1% of patients had a TTR !70%.…”
mentioning
confidence: 99%